KESADARAN DAN SANKSI TERHADAP KEPATUHAN MEMBAYAR PAJAK BUMI DAN BANGUNAN DENGAN PARTISIPASI SEBAGAI VARIABEL MODERATING - Wastam Wahyu Hidayat (Jurnal Akuntansi dan Pajak, 2023)
This study aims to determine the effect, awareness, and sanction on taxpayer compliance with participation as memorization. The sample used in the study was 100 taxpayers. The data collection technique in this research is simple random sampling. Data processing with Linear Regression Analysis Test using SPSS version 24. The results of this study indicate that: taxpayer awareness affects taxpayer compliance, tax sanctions have a positive effect on taxpayer compliance; and taxpayer awareness is not able to moderate the relationship between mandatory awareness and taxpayer compliance, while tax sanctions can moderate the relationship between tax and taxpayer compliance. The research shows that the adjusted R Square figure is 0.567 or 56.7%, meaning that taxpayer compliance can be explained by the variables of tax awareness and public participation, while the remaining 43.3% is explained by other factors.